Cross-cultural applicability and reduction of the American seven-subtest short form of the WAIS on a Swedish non-clinical sample. Issue 3 (3rd July 2019) - Maria, Lindau; Mats, Najström
Abstract: The study aimed at investigating whether the seven-subtest short form based on WAIS-R (Ward1990 ) was statistically valid to use on the Swedish version of Wechsler Adult Intelligence Scale, Fourth Edition (WAIS-IV), if this abbreviation was fit to catch the heterogeneity in test performance across age and if this brief measure was possible to abbreviate even more. WAIS-IV data from a non-clinical sample consisting of 261 participants ranging between 18 and 74 in age was analyzed with bivariate and multiple regression analyses, a prorating method for calculation of Full Scale IQ (FSIQ) and its indices as well as paired-samples t -test. The results were contradictory. When the original WAIS-IV was compared to the seven-subtest short form the results showed a good congruence on FSIQ-level between the two sets, but on index level there were several cases of mismatches. In the younger and middle aged sample (<55 years) results on FSIQ as well as index level were in accordance, whereas in the elderly group (∼55 years) they were incongruent. The best reduction of the seven-subtest short form was a four-subtest model, encompassing Block Design, Similarities, Arithmetic and Coding, one subtest from each index, but the t -tests indicated several cases of mismatches between the full WAIS-IV measures and the prorated scores. Applied on the Swedish version of the WAIS-IV the seven-subtest formula appears to be applicable on an FSIQ level, to be suitable for a younger sample, but not for an elderly. Otherwise, this model and the four-subtest model are recommended to be used with caution.